Advertising Effectiveness of Different Media in Promoting Technology-Oriented Ideas among Young Consumers: A Multidimensional Study. Issue 4 (1st October 2016) - Chowdhury, Tamgid Ahmed; Tushi, Tasmia Ekram
ABSTRACT: Historically, media choice criteria have mostly been company driven. This article offers a four-dimensional 17-item media effectiveness assessment index as perceived by young consumers. The methodology of the study is based on quantitative data collected from 1, 257 respondents in Bangladesh. Radio was rated best in six out of 17 criteria whereas TV and billboard were found to be the second choice. Radio was found to be the most effective medium in creating purchase intention. As the study didn't find complete domination by any single medium, the paper recommends a mixed-media strategy while dealing with young consumers.